Type Design of Continuous Stirred Tank Reactors (CSTRs) for Bath Bomb Lavender Production - Nissa, R. Namira Atha (Universitas Negeri Medan, 2024)
One of the most widely used complimentary bath products is lavender bath bomb, which has a pleasant scent, a foamy feel, and a relaxing effect. This is a chance to expand the production of bath bombs. The manufacture of lavender bath bombs on a large scale (industry) can be done using a continuous stirred tank reactors (CSTRs). This research aims to design a reactor to react the raw materials of lavender bath bomb through mixing reaction. The method used is by conducting computational analysis and calculation of the reactor and its stirrer and mass balance as the basis for calculation using Microsoft Excel. According to the computation results, the examined reactor needs one stirrer with a power of 141 horsepower and a total volume of 7.2334 ft3 with a height of 27.1045 in. These computational and analytical results can describe the production system using the reactor as a learning tool.